2017
DOI: 10.1016/j.ejpoleco.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

On the historical roots of women's empowerment across Italian provinces: religion or family culture?

Abstract: Women should remain silent in the churches. They are not allowed to speak, but must be in submission, as the law says. (Corinthians 14:34) Older women likewise are to be reverent in their behavior,[...] they may encourage the young women to love their husbands, to love their children, to be sensible, pure, workers at home, kind, being subject to their own husbands, that the word of God may not be dishonored. (Titus 2:3-5) To the woman he said, "I will surely multiply your pain in childbearing; in pain you shal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 73 publications
(40 reference statements)
1
16
0
Order By: Relevance
“…Once again, as for nineteenth-century indicators, the nuclear family type emerges as a consistent correlate of several dimensions of the socio-economic level of development. To conclude, in line with the evidence presented by Bozzano (2016), our long-run implications of the historically-determined marriage patterns across Italian provinces appear to be related to the transmission of cultural norms in favor of more gender equality. Indeed gender roles are historically determined and might have path-dependent effects on current women's outcomes through cultural intergenerational transmission and are mainly attached to heritage and traditions (Bisin and Verdier, 2000;Guiso et al, 2006).…”
Section: Short-and Long-run Implications Of Family Structuresupporting
confidence: 84%
See 3 more Smart Citations
“…Once again, as for nineteenth-century indicators, the nuclear family type emerges as a consistent correlate of several dimensions of the socio-economic level of development. To conclude, in line with the evidence presented by Bozzano (2016), our long-run implications of the historically-determined marriage patterns across Italian provinces appear to be related to the transmission of cultural norms in favor of more gender equality. Indeed gender roles are historically determined and might have path-dependent effects on current women's outcomes through cultural intergenerational transmission and are mainly attached to heritage and traditions (Bisin and Verdier, 2000;Guiso et al, 2006).…”
Section: Short-and Long-run Implications Of Family Structuresupporting
confidence: 84%
“…Bertocchi and Bozzano (2016) explore the link between family culture and medieval commerce, a factor which is also associated with gendered human capital accumulation, and establish a positive and significant correlation between medieval commerce and the diffusion of the egalitarian family type with late marriage. Bozzano (2016) investigates the impact of family culture on present-day women's empowerment across Italian provinces and finds a strong and persistent effect of inherited family culture as measured by the prevailing fertility norms in the early twentieth century, as well as a significant association with the Todd family types. Indeed provinces with higher fertility rates in the past, which implied a more subordinated and caring role of women, are still characterized today by lower degrees of equality between sexes especially in top managerial positions.…”
Section: Short-and Long-run Implications Of Family Structurementioning
confidence: 99%
See 2 more Smart Citations
“…[ 11 ] A study in Italy showed that empowerment of women is significantly related to social norms about culture, women's roles in society and especially religious culture. [ 12 ] Another longitudinal study on married women showed the role of financial empowerment, and women's decision-making power in households[ 13 ] and a study in England showed that promotion of gender equality is one of the methods for the empowerment of women and improving their mental health. [ 14 ] Scientific studies also show that women's mental health is endangered when they are faced with gender discrimination such as nonequal access to education, society and employment.…”
Section: Introductionmentioning
confidence: 99%